Topography analysis using wearable devices and its integration in navigation systems - Domb Menachem, S; Sanjay, Sanjay (International Journal of Engineering and Technology, 2018)
Automatic navigation in an unknown environment raises various challenges as many cues about orientation are difficult to perceive without the use of vision. Though assisted aids such as GPS devices help in route finding, still it fails to fulfill safety requirements. This paper proposes a framework that provides accurate guiding and information on the route traversal and the topography of the road ahead. The framework is composed of technologies such as Lumigrids, Drone, GPS, Mobile applications, Cloud storage which are used to map the road surface and generate proper navigation guidance to the end user. This is done in three stages; [1]. Off-line mapping of the road surface and storing this information in the cloud. 2. Wearable technology used for obtaining in real-time surface information and comparing it to the data on the cloud facilitating accurate and safer navigation 3. Updating the cloud information with information collected by the pedestrian Â